PEMBENTUKAN KARAKTER RELIGIUS SISWA MELALUI PEMBIASAAN SHALAT DLUHA DI MADRASAH ALIYAH SUNAN AMPEL KRATON - Aris Fajaruddin (Tarbawi : Jurnal Studi Pendidikan Islami, 2024)
The practice of religious teachings, in terms of forming religious character, can be done by socializing congregational prayers in the madrasah environment. The application of prayer, especially the dluha prayer in the madrasah environment is expected to provide encouragement/motivation to improve education in Indonesia.The aim of study was to determine the Strategy for Forming the Religious Character of Students Through the Habit of Dluha Prayer at Madrasah Aliyah Sunan Ampel and its inhibiting and supporting factors, using an interview approach and using data analysis methods in the form of data reduction. The results of this study include the formation of the religious character of Students at Madrasah Aliyah Sunan Ampel Kraton, namely the habit of praying dluha in congregation which is carried out in the mosque. The supporting factors are the cohesiveness of the teacher board and the integration between the madrasa and the pesantren, as well as the location of the madrasa which is also within the pesantren environment. The inhibiting factor is that there are students who ignore the obligatory schedule of the dluha prayer so that it can inhibit the formation of religious character for students.